Deep Talk sebagai Pola Komunikasi Efektif dalam Keluarga - Langgeng Fajar Miftahul Ilmi (Gunung Djati Conference Series, 2023)
This research is motivated by the many cases of the failure of one's interpersonal communication with parents. This research also aims to find out how deeptalk can be an effective form and pattern of communication in improving family relationships. This research uses qualitative research with descriptive-analytical analysis. This research shows that deeptalk communication pattern in which there is a deep conversation between children and parents can make family life more harmonious because both children and parents understand each other's situation.